Concurrent transfection of randomized transgene configurations into targeted integration CHO host is an advantageous and cost‐effective method for expression of complex molecules. Issue 4 (30th December 2020) - Dong, Emily; Lam, Cynthia; Tang, Danming; Louie, Salina; Yim, Mandy; Williams, Ambrose J.; Sawyer, William; Yip, Shirley; Carver, Joseph; AlBarakat, Ali; Tsukuda, Joni; Snedecor, Brad; et al.
Abstract: Complex recombinant proteins are increasingly desired as potential therapeutic options for many disease indications and are commonly expressed in the mammalian Chinese hamster ovary (CHO) cells. Generally, stoichiometric expression and proper folding of all subunits of a complex recombinant protein are required to achieve the desired titers and product qualities for a complex molecule. Targeted integration (TI) cell line development (CLD), which entails the insertion of the desired transgene(s) into a predefined landing‐pad in the CHO genome, enables the generation of a homogeneous pool of cells from which clonally stable and high titer clones can be isolated with minimal screening efforts. Despite these advantages, using a single transgene(s) configuration with predetermined gene dosage might not be adequate for the expression of complex molecules. The goal of this study is to develop a method for seamless screening of many vector configurations in a single TI CLD attempt. As testing vector configurations in transient expression systems is not predictive of protein expression in the stable cell lines and parallel TI CLDs with different transgene configurations is resource‐intensive, we tested the concept of randomized configuration targeted integration (RCTI) CLD approach for expression of complex molecules. RCTI allows simultaneous transfection of multiple vector configurations, encoding a complex molecule, to generate diverse TI clones each with a single transgene configuration but clone specific productivity and product qualities. Our findings further revealed a direct correlation between transgenes' configuration/copy‐number and titer/product quality of the expressed proteins. RCTI CLD enabled, with significantly fewer resources, seamless isolation of clones with comparable titers and product quality attributes to that of several parallel standard TI CLDs. Therefore, RCTI introduces randomness to the TI CLD platform while maintaining all the advantages, such as clone stability and reduced sequence variant levels, that the TI system has to offer. Abstract : Randomized Configuration Targeted Integration (RCTI) cell line development (CLD) approach allows simultaneous transfection of several vectors with different transgene copy numbers and configurations to generate a pool of TI cells each with stable integration of one vector. Subsequent single cell cloning of the pool of TI cells allows isolation of TI clones with different vector configurations, increasing the chance of identifying cell lines capable of expressing complex or difficult to express molecules. RCTI allows introducing randomness to the TI CLD platform in an orderly fashion, while maintaining all the advantages that TI system has to offer, such as clone stability and reduced sequence variant levels.